Las maestras parvularias a inicios del Siglo XX en Chile. Infant school teachers at the beginning of the 20th century in Chile - Estela Socías Muñoz (Cabás)
(ES) El artículo nos describe la evolución de la enseñanza parvularia en Chile. Podemos ver cómo ya en el periodo precolombino existía una atención en los primeros años del niño. A mediados del XIX existían los llamados “grupos de juego” y también algunos kindergarten. La influencia fröebeliana se hace cada vez más patente. A principios del siglo XX la necesidad de trabajar de las madres chilenas hace surgir la idea de una educación preescolar mantenida por el estado. Se forma la Asociación de Maestras de Kindergarten. A mediados de este siglo se funda la Escuela de Educadoras de Párvulos. Desde aquella década la educación de párvulo fue desarrollándose de manera más profesional y con una serie de cambios que fueron generando mejores condiciones para su implementación permanente. (EN) The article describes the development of preschool education in Chile. We can see how as fas as in the pre-Columbian period there was a focus on the early years of the child. At the middle of the nineteenth century, we found what were called "play groups" and some kindergarten. The fröebeliana influence is increasingly apparent. In the early twentieth century, the need for work of Chilean mothers raises the idea of a preschool education maintained by the state. The Kindergarten Teachers Association is formed. At the middle of the twentieth century, a School for Infant Teachers is founded. From that decade, infant education was developed more professionally and with a number of changes that generated better conditions for a permanent deployment.